Mixed adenoneuroendocrine carcinoma with loss of HER2 positivity after trastuzumab-based chemotherapy for HER2-positive gastric cancer: a case report - Hiromi Nagata; Hironori Tsujimoto; Yoshihisa Yaguchi; Keita Kouzu; Yujiro Itazaki; Yusuke Ishibashi; Satoshi Tsuchiya; Takao Sugihara; Nozomi Ito; Manabu Harada; Shinsuke Nomura; Yoshitaka Utsumi; et al. (Surgical Case Reports)
Abstract Background Trastuzumab (T-mab)-based chemotherapy is a standard regimen for human epithelial growth factor 2 (HER2)-positive gastric cancer. However, some patients have demonstrated a change in HER2 status after T-mab-based treatment of breast cancer. We report a rare case of mixed adenoneuroendocrine carcinoma with loss of HER2 positivity after T-mab-based chemotherapy for HER2-positive gastric cancer. Case presentation A 60-year-old man presented with a mass of the upper abdomen, which was diagnosed as adenocarcinoma with a HER2 score of 3+ by endoscopic biopsy. He received seven cycles of combination chemotherapy with capecitabine, cisplatin, and T-mab. Subsequently, he underwent open total gastrectomy, distal pancreatosplenectomy, and extended left hepatic lobectomy as a conversion surgery. The surgically resected specimen demonstrated both adenocarcinoma and neuroendocrine components; therefore, it was diagnosed as HER2-negative mixed adenoneuroendocrine carcinoma. Although the patient received additional chemotherapy, multiple liver metastases appeared at 3 months postoperatively and he died at 6 months postoperatively because of the rapidly progressing metastatic tumor. Conclusions We encountered a rare case of rapidly progressive mixed adenoneuroendocrine carcinoma that was negative for HER2 expression after T-mab treatment combined with chemotherapy.